Spectrophotometric Determination of Fe(III), V(V) and Cu(II) Using Some Hydroxamic acid Derivatives - Roushdy, M.I.; Issa, Y.M.; El-Zein, S.M.; El-Deen Harb, F.M.S. (Asian Journal of Chemistry, 2010)
New, simple, rapid and accurate methods for the spectro- photometric determination of Fe(III), V(V) and Cu(II) using N-benzoyl-N-phenylhydroxamic acid and four of its derivatives and N-furoyl-N-phenyl-hydroxamic acid are described. The optimum conditions favouring the formation of coloured complexes are extensively studied. The stoichiometric ratios of the formed complexes were 1 : 1, 1 : 3 (M : L) for Fe(III), 1 : 3 (M : L) for V(V) and 1 : 1, 1 : 2 (M : L) for Cu(II). The stability constants were determined applying spectrophotometric methods. Beer's law was found to be obeyed up to 4.48, 4.49 and 5.67 μg/mL for Fe(III)-(1a–1f), V(V)-(1a–1f), and Cu(II)-( 1a–1f) complexes, respectively. The molar absorptivity, specific absorptivity, Sandell sensitivity and Ringbom optimum range are given. Spectrophotometric and direct titration methods using EDTA are suggested and the named hydroxamic acid derivatives as indicators. The applicability of using ligand (III) for the detrmination of Fe and V in crude oils has been evalutated.